2018
DOI: 10.1186/s12974-018-1224-3
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow-derived mesenchymal stem/stromal cells reverse the sensorial diabetic neuropathy via modulation of spinal neuroinflammatory cascades

Abstract: BackgroundDiabetic neuropathy (DN) is a frequent and debilitating manifestation of diabetes mellitus, to which there are no effective therapeutic approaches. Mesenchymal stem/stromal cells (MSC) have a great potential for the treatment of this syndrome, possibly through regenerative actions on peripheral nerves. Here, we evaluated the therapeutic effects of MSC on spinal neuroinflammation, as well as on ultrastructural aspects of the peripheral nerve in DN-associated sensorial dysfunction.MethodsC57Bl/6 mice w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 74 publications
2
45
0
Order By: Relevance
“…Wang, Ma, et al, 2018) Bone and cartilage diseases (Jo et al, 2014;Kastrinaki et al, 2013) Autoimmune diseases (Xu, 2018;W. Zhang, Feng, et al, 2018) Amyotrophic lateral sclerosis (Bonafede & Mariotti, 2017) Diabetes (Evangelista et al, 2018;Gabr et al, 2018) Glaucoma (Manuguerra-Gagne et al, 2013;Osborne, Sanderson, & Martin, 2018;Roubeix et al, 2015) Graft vs host disease (Jurado et al, 2017;Zhao et al, 2015) Intervertebral disc disease (Ahn et al, 2015;Beeravolu et al, 2018;Pereira et al, 2016;Perez-Cruet et al, 2018) Multiple sclerosis (Harris et al, 2018;Nasri et al, 2018;Planchon et al, 2018) Myocardial infarction ( investigated for the treatment of chronic tissue ulcers caused by diabetes. Patients were administered with MSCs for skin healing showed an improvement in microvascularisation structure (Kirana et al, 2012).…”
Section: Promising Applications Referencementioning
confidence: 99%
See 1 more Smart Citation
“…Wang, Ma, et al, 2018) Bone and cartilage diseases (Jo et al, 2014;Kastrinaki et al, 2013) Autoimmune diseases (Xu, 2018;W. Zhang, Feng, et al, 2018) Amyotrophic lateral sclerosis (Bonafede & Mariotti, 2017) Diabetes (Evangelista et al, 2018;Gabr et al, 2018) Glaucoma (Manuguerra-Gagne et al, 2013;Osborne, Sanderson, & Martin, 2018;Roubeix et al, 2015) Graft vs host disease (Jurado et al, 2017;Zhao et al, 2015) Intervertebral disc disease (Ahn et al, 2015;Beeravolu et al, 2018;Pereira et al, 2016;Perez-Cruet et al, 2018) Multiple sclerosis (Harris et al, 2018;Nasri et al, 2018;Planchon et al, 2018) Myocardial infarction ( investigated for the treatment of chronic tissue ulcers caused by diabetes. Patients were administered with MSCs for skin healing showed an improvement in microvascularisation structure (Kirana et al, 2012).…”
Section: Promising Applications Referencementioning
confidence: 99%
“…Wang, Zhang, Shen, Zhang, & Gu, 2018;, myocardial infarction (X. Q. Chen et al, 2014), and type 1 diabetes mellitus (Evangelista et al, 2018). It has also been shown that the use of chemokines and cytokines derived from MSCs improved the treatment efficacy for autoimmune disease (M. Wang, Yuan, & Xie, 2018;Xu, 2018;W.…”
mentioning
confidence: 99%
“…Some studies have shown that BMSCs expressed genes and proteins related with the neural lineage, and have been displayed to hold neurogenic differentiation potential the proper conditions in vitro [44][45][46] . BMSCs transplantation restrained multiple parameters of spinal neuroin ammation found in diabetic mice 47 . BMSCs can release neurotrophic factors, including GDNF and BDNF to protect neurons 48,49 .…”
Section: Discussionmentioning
confidence: 92%
“…Some studies have shown that BMSCs expressed genes and proteins related with the neural lineage, and have been displayed to hold neurogenic differentiation potential the proper conditions in vitro [40][41][42] . BMSCs transplantation restrained multiple parameters of spinal neuroinflammation found in diabetic mice 43 . It is important that BMSCs can release neurotrophic factors, including GDNF and BDNF to protect neurons 44,45 .…”
Section: The Vivo Effects Of Inducing Cellsmentioning
confidence: 92%